Silence and Self-Discovery in Contemporary Writing (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Silence has emerged as a powerful literary device in contemporary writing, representing not merely the absence of speech but also a profound medium of self-exploration and inner awakening. Contemporary authors frequently employ silence to portray emotional trauma, identity crises, alienation, and spiritual reflection. This research paper examines how silence contributes to self-discovery in selected contemporary literary works. Through psychological, philosophical, and literary perspectives, the paper analyzes how characters withdraw from external chaos to encounter their authentic selves. The study further highlights that silence functions as resistance, healing, introspection, and transformation in modern literature. By examining works of writers such as Virginia Woolf, Sylvia Plath, Franz Kafka, Arundhati Roy, Kazuo Ishiguro, Paulo Coelho, and Haruki Murakami, the paper argues that silence becomes a pathway toward identity, emotional healing, and existential understanding in contemporary literature.